Pengaruh Stres Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Logistik Pt.Mitra Angkutan Sejati - Leni, Nur (BISMA : Business and Management Journal, 2024)
One of the keys to the success of an institution is job satisfaction. Job satisfaction is a very important factor in getting optimal work results. The various tasks given to employees will be effective if they feel satisfied with their work. Basically, job satisfaction is an individual thing because each individual will have a different level of satisfaction according to the values that apply to each individual. The more aspects of the job that suit the individual's desires, the higher the level of satisfaction felt.Research subject are all employees of PT. Mitra Angkutan Sejati, and the object of research is work stress, satisfaction work, and employee performance. The population in this study was 35 employees. All of these populations used as the unit of observation, so this research is population research. Collection technique The data in the research are (1) recording documents, and (2) questionnaires, then analyzed using path analysis. The research results show that there is an influence from (1) work stress and job satisfaction on employee performance, (2) work stress has a negative effect on satisfaction work, (3) work stress has a negative effect on employee performance, and (4) job satisfaction has a positive effect on employee performance at PT. Mitra Angkutan Sejati.